2020
DOI: 10.1007/s12671-020-01557-6
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and self-compassion as mediators of the Mindful2Work Training on perceived stress and chronic fatigue

Abstract: Objective There is increasing evidence that mindfulness-based interventions reduce stress and improve wellbeing in employees. However, less is known about the factors that mediate these effects. The aim of this study was to assess short-and long-termmediating effects of mindfulness and self-compassion on the effects of the Mindful2Work training. Methods Employees with burnout complaints (N = 124) filled in questionnaires concerning perceived stress, chronic fatigue, mindfulness, and self-compassion. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This result may be explained by the self-regulatory capacity of mindfulness (Brown & Ryan, 2003). In addition, mindfulness training improves the efficiency of self-regulation and presentmoment attention and awareness, thereby leading to less mental fatigue (Kudesia et al, 2020;van der Meulen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be explained by the self-regulatory capacity of mindfulness (Brown & Ryan, 2003). In addition, mindfulness training improves the efficiency of self-regulation and presentmoment attention and awareness, thereby leading to less mental fatigue (Kudesia et al, 2020;van der Meulen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research has suggested that increased mindfulness by mindfulness training can compensate for cognitive resources and led to less mental fatigue (Kudesia et al, 2020). Indeed, mindfulness was negatively associated with fatigue (Brown & Ryan, 2003;van der Meulen et al, 2021). Similarly, individuals with low mindfulness experience increased burnout when they use social media at work, whereas employees with a high level of mindfulness decrease their burnout when they use social media at work (Charoensukmongkol, 2016).…”
Section: Social Media Fatigue As a Mediatormentioning
confidence: 99%
“…These results were contrary to the findings of the study by Finley et al, (2015); they stated that self-compassion features as an internal resource that reduces caregiver fatigue (Finley et al, 2015). As well, Van der Meulen et al, (2021) in research with the title Mindfulness and self-compassion as mediators of the Mindful2WorkTraining on perceived stress and chronic fatigue found that during and after the training, increases in mindfulness led to more self-compassion, which in turn led to less stress and after the training also to less fatigue. This finding could be explained by a variety of factors.…”
Section: Discussionmentioning
confidence: 96%